PENGARUH EDUKASI TATALAKSANA TIDUR DAN PIJAT KAKI TERHADAP NILAI ANKLE BRACHIAL INDEX (ABI) PADA PENDERITA DIABETES MELITUS TIPE 2 DI WILAYAH KERJA PUSKESMAS KOTA BENGKULU - Heriyanto, Hendri; Mardiani, Mardiani (Mitra Raflesia (Journal of Health Science), 2024)
Background : Diabetes Mellitus (DM) is a group of metabolic diseases characterized by hyperglycemia or high levels of glucose in the blood due to impaired insulin secretion, decreased insulin action or a result of both. The risk of developing type 2 diabetes will continue to increase with increasing age, obesity, and lack of physical activity (American Diabetes Association, 2018). Objective: To determine the effect of providing sleep management books and foot massage on ankle brachial index (ABI) values in patients with type II diabetes mellitus. Research Methods: The design used in this study was One group pre test - post test design, where in this study the sample was observed first before being given treatment then after being given treatment the sample was re-observed (Hidayat, 2007). Results: The results of statistical tests with the Wilcoxon Sign Rank Test at α 5% obtained a Ankle Brachial Index value (p value 0.000 <0.05). Ha accepted. Conclusion: there is an effect of sleep management books and foot massage on changes in Ankle Brachial Index values.Keywords : Ankle Brachial Index, Foot Massage, Sleep Management Book, Diabetes mellitus type 2